(untitled) (Journal of Population and Development, 2023)
The human society has different religion, thought and cultures. The religion is to make the human race as more civilized and disciplined than other beings. The different human societies have their peculiarities in these manners but the similarity among different cultures and communities brings harmony in the society. This article objectifies to have a great respect to all the culture and religions without any biasness. It is notable that the two perspectives of seeing a thing or event in our culture give different meanings which are purely a cultural perspective, and the political perspective. Despite having good ideas on these two heads, sometimes an excellent author even can slip erroneously to blend the pure event with the politics. This article selects a very recent Nepali literary text, Culture Thought, as an experimental material to examine the question raised here. This qualitative research renders throughout the text as per the set of definition of culture and its traits to bring out the political manner as crystal clear from the mixed ideas. It is essential for a healthy relation among religions, countries and their diversified cultures. As this selected experimental book, Culture Thought, has richness in cultural matter, it has some political ideas underlying throughout it which draw a line among nations of South Asia.